Compostagem de resíduos de unidade frigorífica de bovinos - Diniz, Brenda Añazco Benites (2022)
Within the meat production chain, and especially in its industrialization, there is considerable generation of organic waste, which must be treated and disposed of properly, in order to avoid damage to the environment. With this, the objective is the production of compost, using waste generated in a slaughterhouse unit, applying the composting process to these, identifying the best arrangement of waste in compliance with Brazilian regulations. The experiment was conducted in two stages, with the first stage intended for the production of humified compost, carried out at the enterprise, which is located in the state of Mato Grosso. The study was conducted in a randomized block design with 4 treatments and 4 replications, evaluated over 90 days. By means of initial characterization of the residues generated in the slaughter of cattle, regarding their C/N ratio; physical-chemical properties, heavy metals, macro and micronutrients, the composition of the treatments to be applied to compost was defined. Thus, bovine ruminal (R) content was used; gray (Cz); sludge from the effluent treatment plant (L1 and L2), in different mixtures. During the composting evaluation period, monitoring of temperature, pH, humidity and physical-chemical characteristics were carried out to verify the stabilization of the compost. At the end of the process, the second phase refers to the validation of these compounds, which evaluated the concentration of heavy metals and the potential for toxicity from their application on lettuce seeds, for dosage of 50% and 100% of extract solubilized from the composted material. All treatments showed satisfactory results, among the treatments applied T1 consisting of a mixture (71:26:3) of rumen, sludge from the primary treatment and ash, showed better results, meeting the parameters established by the regulations as a reference. The compounds obtained at the end of the process, for the applied treatments, did not point to toxicity, and confer T1 as the best treatment for a dosage of 50%, all values presented confer positive agronomic qualities to the compound.